Análise da multifuncionalidade de usos em diferentes setores censitários do município de São Carlos, São Paulo, Brasil - Dorici, Mariana (2017)
The spaces occupied by the cities have increased significantly in the last decades. In a short period of time, a number of development models were implemented in a disorganized and insufficient way, based on exclusionary plans, which left a significant part of the population without basic services and generated diverse environmental problems, presenting risks to the quality of life and the maintenance of the environment for future generations. Such problems have led to the emergence of new models and planning visions to ensure the conservation of natural resources and the more sustainable life, that is, of higher quality of life for people. These models seek to build more compact cities that require less energy input so that the general population can access the urban infrastructure and equipment demanded (housing, commerce and services). This study aimed at identifying and analyzing the multiplicity of urban uses in previously delimited areas of the city of São Carlos, SP, in order to propose improvements in its functionality to maintain quality of life. Secondary information was used from the 2010 census was made available by the Brazilian Institute of Geography and Statistics (IBGE), mapping GPS, satellite images, GIS software, questionnaires at home and a series of evaluative analyzes of different aspects of urban space. In general, the methodologies used in this study satisfactorily fulfilled their role in the investigation of the study area and allowed all proposed results to be found. These methodologies can be replicated in other places to obtain the same type of results, which are primary in the diagnosis of the urban environment and can compose a series of associations with other essential data in the construction of cities closer to sustainability. With the results found in this research, we realized that without the adequate structure and the change of cultural perspectives, still intrinsic in our society, that reflect in the way of planning and using urban environments, cities or places with compact and dense architectures can generate similar environments or even less attractive than those not based on such structures. As evidenced in the chapters of this dissertation, the dynamics of each site is particular and has its own peculiarities, so the pretension to implant new management modes of urbanized areas must take into account in-depth studies of the different physical and socioecological aspects. It is necessary that the different variables that interfere in the affirmations of these models are analyzed so that the expected result is as close as possible to reality and guarantees that improvements are actually achieved.